BREAST CANCER THERAPY: NEW TREATMENT METHODS FOR BREAST CANCER - Fayzullaeva Madina Bakhshillo kizi; Maxarova Moxinur Baxtiyor qizi; Sodiqova Nigoraxon Sodirjon qizi; Sindorova Jasmina Farxod qizi (TADQIQOTLAR, 2025)
Annotation: This article explores recent advancements in the treatment of breast cancer, focusing on innovative therapeutic approaches such as immunotherapy, targeted therapy, and personalized medicine. The study reviews clinical trials and scientific literature to highlight how these new methods improve patient outcomes, reduce side effects, and enhance survival rates. By comparing traditional treatments with modern techniques, the article provides insight into the evolving landscape of breast cancer management and outlines future directions in oncological care.